Keterampilan Mendeklamasikan Puisi melalui Model Pembelajaran Somatis, Auditori, Visual, dan Intelektual (SAVI) - Mochamad Widi Santoso; Miftahulkhairah Anwar; Gusti Yarmi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to improve poetry reciting skills using SAVI learning model for fourth grade students of SDN 2 Kejiwan. This action research study uses three research instruments. That is teacher performance, test instruments, and questionnaire instrument data in the form of student responses. In pre-research, the test of reciting poetry got 68.03%. In the first cycle, after applying the SAVI model, there was an increase in the average value of the tests recite poetry is 77.58%, the second cycle being 88.03%. Teacher performance in applying the model for 5 meetings in the first cycle received an average value of 92.74% (very good), the second cycle the value of teacher performance in applying the SAVI model obtained an average of 100% perfect score. The response of students in the first cycle get a good response with a value of 86.92%, and the second cycle the response of students increased to 94.24% with very good criteria. Based on these data, it can be concluded that the SAVI learning model can improve the poetry reciting skills of fourth grade students at SDN 2 Kejiwan. Keywords: SAVI Learning Model, Reciting Poetry